2019
DOI: 10.17126/joralres.2019.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the manual manipulation of composite resin with latex gloves

Abstract: Efecto de la manipulación manual de resina compuesta con guantes de látex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…At one-month post-photocuring, the control group recorded a signi cantly higher compressive strength mean value when compared to one-day post-photocuring value. Our ndings con rmed the results of Gornig et al [29]. However, the contaminated groups showed no signi cant difference between compressive strength mean value at one-day and onemonth post-photocuring.…”
Section: Discussionsupporting
confidence: 91%
“…At one-month post-photocuring, the control group recorded a signi cantly higher compressive strength mean value when compared to one-day post-photocuring value. Our ndings con rmed the results of Gornig et al [29]. However, the contaminated groups showed no signi cant difference between compressive strength mean value at one-day and onemonth post-photocuring.…”
Section: Discussionsupporting
confidence: 91%
“…It was previously postulated that manual manipulation of resin composite with powdered latex gloves should be avoided [ 30 ]. Martins et al [ 12 ] found that the flexural strength of resin composite manipulated with powdered gloves was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Martins et al [ 12 ] found that the flexural strength of resin composite manipulated with powdered gloves was reduced. It was previously revealed that sulfides released from latex gloves inhibited the polymerization of the silicone in impression materials based on polyvinyl siloxanes, when it reacts with chloroplatinic acid from silicones [ 30 ]. The results of the current study confirmed previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that the direct contact of gloved hands on the composite resin will contaminate the material due to the powder added on the latex gloves. The contamination with gloves powder can reduce the cohesive strength [ 7 ] and microhardness [ 8 ] of the composite, consequently jeopardizing the quality and durability of the restoration [ 7 , 9 ]. Adhesive systems used as lubricants to gain flowability may also impair the restoration, creating small defects and propagating pre-existing cracks in between the incremental layers of the composite resin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%